Peran Mediasi Kepuasan Kerja terhadap Kinerja Organisasi pada PT ABC - Muhammad Farhan Fahrezy; Arief Alfiandry (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
This study examines how employee empowerment and training influence perceived organizational performance, with job satisfaction as a mediating variable, at PT ABC, focusing on the security division. Using a quantitative survey approach with 102 respondents selected through saturated sampling, data were collected via Likert-scale questionnaires and analyzed using SEM-PLS via SmartPLS 4.0. The results indicate that empowerment, training, and job satisfaction significantly affect perceived organizational performance. Furthermore, empowerment and training positively influence job satisfaction, which mediates their relationship with perceived performance. The findings of this study provide important implications for both theory and practice. From a theoretical perspective, this study strengthens the literature in human resource management and organizational behavior, particularly regarding the role of job satisfaction as a mediating variable in enhancing organizational performance. Practically, the results suggest that companies should prioritize employee empowerment and continuous training programs as strategic tools to improve job satisfaction and ultimately enhance perceived organizational performance. Organizations are encouraged to create supportive work environments, involve employees in decision-making processes, and design relevant training initiatives aligned with job requirements. These strategies are expected to increase employee engagement, reduce turnover intentions, and foster sustainable organizational performance.